Classifying Functioning of Children and Adolescents with Intellectual Disability: The Utility of the International Classification of Functioning, Disability and Health for Children and Youth - Vale, Maria do Carmo (2017)
Observational cross-sectional study carried out in a pediatric neurodevelopment unit of a tertiary-care hospital. A sample of 355 children with median ((min.–max.) 1.0–17.3) years with intellectual disability (30.4% borderline, 43.1% mild, 19.7% moderate, 5.1% severe, and 1.7% profound disability) was seen over a period of 3 years. Based on clinical observation and psychological evaluation, a neurodevelopmental pediatrician selected ICF-CY body functions codes, and respective qualifiers, to effectively describe functioning of children. Based on evaluation reports, a psychologist and a special educator assigned the previously chosen ICF-CY body functions codes to 139 and 67 children, respectively. Inter-rater agreement was estimated using simple and weighted Cohen’s kappa coefficients and Gwet’s AC1 statistic and Gwet’s weighted kappa coefficient statistic. A set of eight ICF-CY codes was identified as efficiently describing impairments of body functions of children with intellectual disability: global mental functions b117 and b122; specific mental functions b147, b163, b164, and b167; and voice and speech functions b320 and b330. Results indicate a correspondence between the level of severity of qualifiers assigned to ICF-CY codes and the level of intellectual disability. Inter-rater agreement was variable among raters, with the best agreements found for qualifying intellectual functions (b117) and psychomotor functions (b122). A profile of eight ICF-CY codes effectively describes functioning of children with intellectual disability, providing an alternative to medically based classification, based on diagnoses with functionally based classification of children’s characteristics. The findings contribute to define a comprehensive set of codes to reliably record individual differences of functioning in this population